(untitled) (Research, Society and Development, 2021)
Objective: Identify and analyze the Brazilian scientific knowledge produced on the perceptions of the puerperal women regarding institutional obstetric violence in the parturitive period. Method: This is an integrative review. For the selection of articles, the following databases were used: LILACS, MEDLINE, SCIELO and BDENF. Results: Seven articles were selected, from which three categories emerged: Violence of a psychological nature: its modes and repercussions, Violence of a physical character and unnecessary procedures and institutional violence and the violation of women’s rights. Conclusion: Sensitization of health professionals and institutions regarding the importance of humanizing childbirth and birth.